Protective role of peroxisome proliferator-activated receptor-β/δ against pulmonary oxygen toxicity mediated through changes in NOS expression levels. (16th March 2014) - Bao, Xiao-Chen; Fang, Yi-Qun; You, Pu; Zhang, Shi; Ma, Jun
ABSTRACT Recent studies have demonstrated that peroxisome proliferator-activated receptor-beta/delta (PPAR-β/δ) has a protective effect during lung injury induced by bleomycin and polymicrobial sepsis, but its function in pulmonary oxygen toxicity is unknown. In this study, we used GW0742, a PPAR-β/δ agonist, and GSK0660, a PPAR-β/δ antagonist, to test the role of PPAR-β/δ in lung injury due to hyperbaric oxygen (HBO2) exposure. Lung injury was induced in rats by HBO2 exposure (2.3 ATA, 100%O2, 8 hours). Sixty male Sprague-Dawley rats were randomly divided into 6 groups: air+vehicle, air+GW0742, air+GSK0660, HBO2+vehicle, HBO2+GW0742, and HBO2+GSK0660. Rats were injected with vehicle or GW0742 (0.3 mg/kg, i.p.) or GSK0660 (1 mg/kg, i.p.) at 1 hour, 6 hours, and 12 hours before either air or oxygen exposure. Administration of GW0742 to rats exposed to HBO2 significantly reduced the observed lung injury, extravascular lung water, total protein levels in bronchoalveolar lavage fluid, and the levels of iNOS and nNOS in the lungs when compared to untreated rats exposed to HBO2. Treatment of rats with GSK0660 exacerbated lung injury and elevated the levels of nNOS and eNOS in the lungs. In addition, nNOS and eNOS knock-out mice were examined. The results indicated that after HBO2 exposure, the lung injury was obviously decreased in the nNOS−/−+GSK0660 mice compared to the wild-type +GSK0660 mice; furthermore, administration of GSK0660 significantly elevated the lung injury in the eNOS−/− mice. Collectively, these data indicate that PPAR-β/δ activation can protect against pulmonary oxygen toxicity in the lungs of rats through changes in the expression of NOS.